Crazy Horse - McMurtry, Larry 1936-2021 (Viking, 1999)
Strips away the tall tales of legend to reveal the essence of Crazy Horse, profiling him as a brilliant and ascetic warrior-hero whose life exemplified Native American tragedy and the end of the untamed West. Legends cloud the life of Crazy Horse, a seminal figure of American history but an enigma even to his own people in his own day. Yet his story remains an encapsulation of the Native American tragedy and the death of the untamed West. Crazy Horse strips away the tall tales to reveal the essence of this brilliant, ascetic warrior-hero. Larry McMurtry's vivid, carefully considered, succinct biography will lure not only his own fans but history buffs, Western enthusiasts, students of all things Native American, and anyone concerned with the white man's atonement and restitution to native peoples. In a portrait that only he could render, Larry McMurtry captures the poignant passing of a time and offers a vibrant new understanding of the mythic Crazy Horse and what he stood for.
Keywords: Crazy Horse <ca. 1842-1877>; Crazy Horse -- ca. ca. 1842-1877; Indianer; Indians of North America -- Biography; Oglala Indians -- Biography; Biografie